Tilken und Sieke — ein Vergleich - Hempel, Lina (ERDKUNDE, 1954)
In this paper an attempt is made to explain the forms of certain small valleys by reference to the activity of man on the cultivated land. ’Tilken’ are boxshaped little valleys which, for example, are found in the loess area of middle Saxony and the hills of southern Lower Saxony. They originated from little V-shaped valleys or sunken roads. The flat bottom consists of alluvial soil-material derived from adjoining arable fields or paths. The ’Sieke’ of the Ravensberg Hills are little valleys of a similar form but according to their origin two types can be distinguished: those which originated from a V-shaped incision and those derived from a shallow depression. The further development of the former is the same as in the case of the tilken. In the case of the latter, the final box shape is due to active human interference, which occurs both unintentionally through ploughing of the adjoining fields and intentionally by flattening and widening the bottom. Tilken and sieke stand in close relationship to soil erosion and occur consequently on rocks which offer little resistance to erosion. Depending on the prevailing size of agricultural holdings and thus intensity of cultivation, formation of tilken is moderately influenced by human activity whereas that of sieke depends on human action to such a degree that they may even be classified as man-made landscape features.